Using a Digital Meditation Application to Mitigate Anxiety and Sleep Problems in Children with ADHD. Issue 7 (May 2022) - Fried, Ronna; DiSalvo, Maura; Farrell, Abigail; Biederman, Joseph
Objective: ADHD affects 11% of children in the United States and is associated with significant levels of anxiety. Although the literature supports mindfulness-based interventions as a promising strategy for managing anxiety, it falls short in the feasibility of digital mindfulness interventions.Method: This study investigated the usefulness of the pediatric version of Headspace, a digital mindfulness program, for reducing stress in 18 children with ADHD. We conducted a 4-week pilot study to evaluate the Headspace digital mindfulness application for children ages 6 to 12 with ADHD. Parents completed the Beck Anxiety Inventory and the Children's Sleep Habits Questionnaire at baseline and endpoint.Results: Participants had an average age of 9.2 years and were 78% male. The Headspace intervention significantly reduced anxiety and sleep problems in children with ADHD.Conclusion: Children with ADHD and comorbid anxiety and/or sleep problems could benefit from a digitally based meditation application. (J. of Att. Dis. XXXX; XX(X) XX-XX)